Conceptualising personal and historical nostalgia - Marchegiani, Christopher A. (Curtin University, 2009)
The purpose of this research was to extend the knowledge on two distinct types of nostalgia; Personal and Historical. Previous empirical research has studied nostalgia only as a unified concept. Two scales were developed and validated to measure these responses independently of each other. Hypotheses were developed based on extant literature which postulated significant changes in cognitive, emotional, attitudinal, and intention responses as a result of the response type. A model incorporating these consumer reactions was extended and tested. Finally, the effects of varying intensities of the two response types were explored independently of each other.An experimental research design was used with a sound methodology developed though previous studies. A variety of statistical techniques deemed appropriate for each step of the analysis was used. These included both qualitative and quantitative techniques including structural equation modelling and multivariate analyses.Results show significant differences in the consumer behaviour responses examined as a result of the type of nostalgic response being elicited. The examined responses of cognition, emotions, attitudes, and intention are of high significance to academics and managers alike. In terms of comparing Personal and Historical Nostalgia to one another, Personal Nostalgia had a tendency to be more beneficial in the majority of consumer reactions. A model of these reactions was successfully extended and shown to differ between the conditions illustrating the need to explore these reactions independently. Varying levels of intensity of each specific nostalgic response type were shown to have significant effects on the examined consumer behaviour responses also. As a very general statement of the findings, it was found to be worthwhile to raise the levels of Personal or Historical Nostalgia to as high a level as possible to significantly positively alter emotions, attitudes, and intention. However, although significant cognitive changes were seen between low and mid levels of each nostalgic reaction, moving to a high level was found to have no significant impact on cognitive reactions.The most significant contributions of the research are the development of the two specific scales independently of each other through seven studies, and substantiating the hypothesised differences between the two responses with empirical evidence. These findings bridge many important gaps in the literature. Personal and Historical Nostalgia had previously only been conceptually discussed, with little to no empirical data, despite evidence of both types in the market place. The varying costs and benefits of evoking the two nostalgic responses, or varying levels of either, were unknown until now. This research results in several conceptual, methodological, and managerial implications especially valuable to academics, strategists, and industry policy makers. It also provides a solid foundation for numerous future studies.